Fundamentals of Rhenium-188 Radiopharmaceutical Chemistry - Janke Kleynhans; Adriano Duatti; Cristina Bolzati (Molecules, 2023)
The β− emitter, rhenium-188 (188Re), has long been recognized as an attractive candidate for targeted cancer radionuclide therapy (TRNT). This transition metal shares chemical similarities with its congener element technetium, whose nuclear isomer technetium-99m (99mTc) is the current workhorse of diagnostic nuclear medicine. The differences between these two elements have a significant impact on the radiolabelling methods and should always receive critical attention. This review aims to highlight what needs to be considered to design a successful radiopharmaceutical incorporating 118Re. Some of the most effective strategies for preparing therapeutic radiopharmaceuticals with 188Re are illustrated and rationalized using the concept of the inorganic functional group (core) and a simple ligand field theoretical model combined with a qualitative definition of frontiers orbitals. Of special interest are the Re(V) oxo and Re(V) nitrido functional groups. Suitable ligands for binding to these cores are discussed, successful clinical applications are summarized, and a prediction of viable future applications is presented. Rhenium-188 decays through the emission of a high energy beta particle (2.12 MeV max energy) and a half-life of 16.9 h. An ideal biological target would therefore be a high-capacity target site (transporters, potential gradients, tumour microenvironment) with less emphasis on saturable targets such as overexpressed receptors on smaller metastases.